Exome Variant Analysis of Chronic Periodontitis in 2 Large Cohort Studies. (January 2017) - Kasbohm, E.; Holtfreter, B.; Völker, U.; Petersmann, A.; Samietz, S.; Biffar, R.; Völzke, H.; Meisel, P.; Kacprowski, T.; Homuth, G.; Kocher, T.; Teumer, A.
Periodontitis is characterized by inflammation of the gingival tissue. The main risk factors are socioeconomic factors, sex, age, smoking, and diabetes, but periodontal disease has also a genetic background. Previous genome-wide association studies failed to reveal genome-wide significant associations of single common single-nucleotide polymorphisms with chronic periodontitis. Using the Illumina ExomeChip data of 6, 576 participants of the German population-based cohort studies Study of Health in Pomerania (SHIP) and SHIP-Trend, the authors performed single variant and also gene-based association studies of rare and common exonic variations on different periodontal case definitions. Although our study comprised the largest sample size to date to assess genetic predisposition for chronic periodontitis, the authors found no significant association. This study emphasizes that for chronic periodontitis, large sample sizes will be necessary to find genetic associations, even when examining rare genetic variants.